BETWEEN FAITH AND FREEDOM: The Qur’an and the Childfree Lifestyle - Qibtiyah, Maria; Badruzaman, Abad (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2025)
This article seeks to discuss the issue of being childfree from the perspective of the Qur’an. The topic has generated considerable debate within Indonesian society, making it essential to conduct further analysis, particularly within the context of a Muslim-majority country. Broadly speaking, public opinion is divided into two groups, each presenting its own arguments. Proponents of the childfree choice view it as a matter of personal autonomy, independent of religious norms. Conversely, opponents argue that the childfree lifestyle deviates from Indonesian social norms, which emphasize that married couples should endeavor to have children. Given the complexity of this issue, this article employs Gadamer’s hermeneutical framework in conjunction with an exegetical approach. It argues that several Qur’anic verses implicitly reject the notion of voluntary childlessness. For instance, Surah al-A‘rāf (7:86) encourages the multiplication of offspring, Surah al-Nahl (16:72) praises the birth of noble descendants, and Surah al-Ra‘d (13:23) mentions that children may serve as a means for their parents to attain paradise. These verses indicate that Islam generally disapproves of married couples who deliberately choose not to have children. However, because the meaning of the text is dynamic and continuously engages in dialogue with contemporary social realities—such as the childfree phenomenon—new interpretations may emerge through a fusion of horizons. In this context, the childfree choice is not explicitly deemed haram but may be tolerated if supported by valid reasons and if it yields certain benefits.